CHICKEN MANURE AS BIOSTIMULANT FOR TOTAL PETROLEUM HIDROCARBON (TPH) REMOVAL IN OIL CONTAMINATED SOIL - Arief Rahman; Mudatstsir, Mudatstsir; Yahya, Husnawati (Lingkar: Journal of Environmental Engineering, 2025)
Oil contamination in the soil might cause degradation on the quality of the soil, which becomes a problem for the environment and the organisms in it, especially the plants. The plants will be unable to grow and develop properly in the degraded soil, which will give a severe negative impact to agricultural sector. Biostimulation can be a good solution in solving soil degradation problem, utilizing microorganisms and biostimulant. The objective of this study is to discover the potential of chicken manure as biostimulant for biostimulation process in the removal of total petroleum hidrocarbon (TPH) as one of the main properties in oil contaminant. In this study, the chicken manure as biostimulant were being mixed with the oil contaminated soil (400 gr), with variation of weight; W1= 50; W2= 100; W3= 150; and W4= 200 gr. Biostimulation process were being observed and analyzed every 7 days for 21 days, and being compared with the soil without biostimulant addition (control). The result shown that biostimulation process using chicken manure in this study can remove up to 66.67% of TPH, from 6% of to 2% (W4 for 21 days), but still unable to fulfill the quality standard given, which is 1%. Based on the result of this research, it can be concluded that biostimulation using chicken manure as biostimulant can be utilized to remove TPH from oil contaminated soil, hence still need improvement to perform better.